2016
DOI: 10.12983/ijsrk-2016-p0028-0032
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Associated Liver Toxicity – The Optimal Dose of Aspirin in Liver Insufficiency

Abstract: Abstract. Acetylsalicylic acid (Aspirin) belongs to nonsteroidal anti-inflammatory drugs (NSAIDs). Numerous studies have proven that aspirin reduces the signs and symptoms of inflammation and exhibited a broad range of pharmacological activities, including analgesic, antipyretic and antiplatelet properties. Previous studies suggested that beside the pharmacological activities aspirin was also associated with the side effects and toxicity of various doses and in various formulations. The present study is perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…(27) who found that histopathological study explained seriousness expanded of sores with expanded medication dosage, vacuolation with direct diffuse degeneration, peri-acinar rot with mellow to direct invasion of gateway zones and mononuclear cells in hepatic tissues analyzed of rats adminstrated diclofenac sodium for 14 days at doses of 100 and 150 mg/kg and this agreement with present study. (21) was found in histopathologically slides treated by aspirin explained that found a mild to moderate portal inflammation, focal cellular swelling, micro vesicular steatosis with cytolysis and this agreement with present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…(27) who found that histopathological study explained seriousness expanded of sores with expanded medication dosage, vacuolation with direct diffuse degeneration, peri-acinar rot with mellow to direct invasion of gateway zones and mononuclear cells in hepatic tissues analyzed of rats adminstrated diclofenac sodium for 14 days at doses of 100 and 150 mg/kg and this agreement with present study. (21) was found in histopathologically slides treated by aspirin explained that found a mild to moderate portal inflammation, focal cellular swelling, micro vesicular steatosis with cytolysis and this agreement with present study.…”
Section: Discussionsupporting
confidence: 93%
“…Liver transaminases (ALT with ALP) are benift biomarkers of liver injury in a patient has some degree of healthy liver function, since ALP can be increased in other affecting organs diseases, ALT is more considered specific for hepatotoxicity (21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation